2019
DOI: 10.1002/uog.19164
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of maternal–fetal transmission of cytomegalovirus after primary maternal infection in the first trimester by biweekly hyperimmunoglobulin administration

Abstract: After a primary maternal CMV infection in the first trimester, HIG administration prevents maternal-fetal transmission up to 20 weeks of gestation. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 26 publications
3
76
1
2
Order By: Relevance
“…Nigro et al 55 reported that CMV HIG therapy was associated with a significantly lower risk of congenital CMV infection, especially symptomatic infection. Recently, a prospective observational study reported that, after a primary maternal CMV infection in the first trimester, biweekly HIG administration at a dose of 200 IU/kg prevented maternal-fetal transmission up to 20 weeks' gestation 56 . Unfortunately, the potential efficacy of HIG was not borne out in a phase-II randomized, placebo-controlled, double-blind study 57 , which found no significant improvement in the risk of transmission, levels of virus-specific antibodies, T-cell mediated immune response, viral DNA in the blood or clinical outcome at birth.…”
Section: Recommendationsmentioning
confidence: 99%
“…Nigro et al 55 reported that CMV HIG therapy was associated with a significantly lower risk of congenital CMV infection, especially symptomatic infection. Recently, a prospective observational study reported that, after a primary maternal CMV infection in the first trimester, biweekly HIG administration at a dose of 200 IU/kg prevented maternal-fetal transmission up to 20 weeks' gestation 56 . Unfortunately, the potential efficacy of HIG was not borne out in a phase-II randomized, placebo-controlled, double-blind study 57 , which found no significant improvement in the risk of transmission, levels of virus-specific antibodies, T-cell mediated immune response, viral DNA in the blood or clinical outcome at birth.…”
Section: Recommendationsmentioning
confidence: 99%
“…Currently, treatment with immunoglobulins or antiviral therapy to prevent intrauterine transmission of CMV in pregnant women with primary CMV infection is not recommended as studies have not yet conclusively shown a benefit (63)(64)(65)(66). Data from a non-randomized study showed that biweekly administration of hyperimmunoglobulin until 20 weeks' gestation successfully prevented maternal-fetal transmission of primary infections (65). These data need to be confirmed by a randomized clinical trial (67); if the results are confirmed, two-weekly intervals for testing seronegative women would be necessary.…”
Section: What Are the Gaps In Our Understanding?mentioning
confidence: 99%
“…IgG-antibodies against gB were shown to be highly neutralizing [18]. Scores of HCMV-specific-IgG reactivity were given on the y-axis, as described by Kagan et al [27] and the number of study participants is shown on the x-axis. A validation experiment was performed, using HIG-spiked whey.…”
Section: Hcmv-specific-igg Antibodiesmentioning
confidence: 99%